Effects of forest management on epiphytic lichen diversity in Mediterranean forests - Aragón, Gregorio; Martinez, I.; Izquierdo, P.; Belinchon, R.; Escudero, A. (APPLIED VEGETATION SCIENCE, 2010)
Question What are the responses of epiphytic lichens to the intensity of management along a large environmental gradient in Mediterranean Quercus forests? Location Central Spain. Methods This study was carried out on 4590 trees located in 306 forest stands dominated by Quercus faginea or Quercus ilex ssp. ballota. The effect of forest management and other predictor variables on several species diversity indicators were studied. Variables modelled were total species richness, cyanolichen richness and community composition. A large number of predictor variables were included: forest fragmentation (patch size, stand variability), climate and topographic (altitude, slope, sun radiation, annual rainfall and mean annual temperature) and intensity of management. General linear models and constrained ordination techniques were used to model community traits and species composition, respectively. Results Total richness and especially cyanolichens richness were significantly and negatively affected by the intensity of management. Lichen composition was influenced by management intensity, climatic and topographic variables and stand variability. Conclusions In Mediterranean forests, human activities related to forestry, agricultural and livestock use cause impoverishment of lichen communities, including the local disappearance of the most demanding species. The conservation of unmanaged forests with a dense canopy is crucial for lichen diversity.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: Community traits; Cyanolichens; Drivers of composition; fragmentation; land use; oak forests; Spain; Variation partitioning